A Multicenter, Prospective, Randomized Controlled Trial to Evaluate the Additional Benefit of a Multistrain Synbiotic (Prodefen®) in the Clinical Management of Acute Viral Diarrhea in Children - Emilia García-Menor MD; Fátima García-Marín MD; Raquel Vecino-López MD, PhD; Gloria Horcajo-Martínez MD; María-José de Ibarrondo Gu; Pedro Gómez-González MD; Syra Velasco-Ortega Pharm; Javier Suárez-Almarza Pharm, BSND; Concepción Nieto-Magro MD, PhD (SAGE Publishing, 2016)
This randomized, open-label study evaluated the additional benefits of the synbiotic Prodefen® in the clinical management of acute diarrhea of suspected viral origin in children between 6 months and 12 years of age. Study outcomes included the duration of diarrhea, the recovery from diarrhea, and the tolerability and acceptance of the treatment. The proportion of patients without diarrhea over the study period was greater in the synbiotic group than in the control group at all study time points, showing a statistically significant difference on the fifth day (95% vs 79%, p < 0.001). The duration of diarrhea (median and interquartile range) was reduced by 1 day in the synbiotic-treated patients (3 [2-5] vs 4 [3-5], p = 0.377). The tolerability of the treatment regimen, as evaluated by the parents, was significantly better in those receiving the synbiotic than in the control group. Overall, 96% of the parents of children receiving the synbiotic reported being satisfied to very satisfied with the treatment regimen. The results of this study indicate that the addition of the synbiotic Prodefen® is a well-tolerated and well-accepted approach that provides an additional benefit to the standard supportive therapy in the management of acute viral diarrhea in children.